Akad Kerjasama (Syirkah) Perspektif Fuqoha’ Empat Madzhab - Zaenol Hasan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This paper discusses shirkah, which is where two people pool their assets to transact so that both owners can benefit. It also explains the sources of law, the pillars of shirkah, the conditions of shirkah, the kinds, types, and the end of shirkah. The method used is literature review. The literature used is sourced from the Qur'an, hadith, opinions of fuqaha, and opinions of Islamic legal experts. Keywords: , , opinions